Exploring accounting hybrid skills in a serious games\' environment - Carvalho, Luciano Bastos de (2022)
Soft skills need to be added to the teaching of hard skills in accounting to meet market demands. Thus, accounting educators seek alternatives to develop these hybrid skills in their students, such as serious games. However, although research show the benefits of these games in education, they also demonstrate risks. The misuse of serious games can harm the scarce learning time, resulting in the non-transfer of knowledge to the student, transfer problem. To minimize these risks, a dimensional framework was developed to guide the educator in the application of the serious game. The framework dimensions are formed by elements of game-based learning, experiential learning theory and theory of planned behavior. The analysis of these elements allowed to structure the serious game environment to help the player enter and remain in the teaching methodology in the practical, social and/or reflective dimensions. The practical dimension aims at exploring hard skills. Soft skills are worked on in the social (communication and collaboration) and reflective (critical thinking and problem solving) dimensions. This framework was validated with arguments from the modern theory of validation. Construct validation allowed validating the interaction of conceptual elements, creating a serious game environment. Content validation demonstrated the hybrid skills that can be explored using games as a teaching methodology. In turn, the related validation arguments integrated the possible hybrid skills of accounting to be explored with the game with the conceptual elements that form the serious game environment. In this way, the framework guides the accounting educator to apply the serious game teaching methodology and explore the desired hybrid skill, minimizing the risks of this pedagogical practice and preparing the student according to market demands. However, this framework does not allow verifying how students are exploring these hybrid skills. Verifying the application of hybrid skills makes it possible to carry out a diagnosis and evaluate the development of these skills. Thus, it is necessary to apply a tool to capture these hybrid skills in the game environment. The games have elements that require technical accounting knowledge, which facilitates the assessment of hard skills. However, no guides were detected to assess soft skills in the serious game environment. So, another framework was developed to fill this new gap. This time, literature reviews were used on (i) the evaluation process in accounting to verify the main requirements for an effective evaluation, (ii) the evaluation of serious games in accounting, to analyze the possible tools for use in this process and (iii) the characteristics of soft skills, to identify how to evaluate them. This literature made it possible to develop a framework that guides the educator to use the tools detected in the soft skills assessment process in the serious game environment, using microsoftskills. Such skills must be relevant to the chosen serious game dimension (practical, social and/or reflective), and the requirements minimize the analysis of false results. This framework was validated and made reliable with the application of the design-based research methodology in three moments of the serious game DANIEL. It is noteworthy that the validation is for the presented environment. Future reseaches may increase the validation range of the frameworks presented in this thesis.